اتجاهات تلاميذ مرحلة التعليم الثانوي نحو خدمات الارشاد النفسي - قصة,حنان; معلول,ايمان (University of Eloued جامعة الوادي, 2024)
هدفت هذه الدراسة الى التعرف على طبيعة اتجاهات تلاميذ الثانوي وبالأخص تلاميذ الثانية ثانوي في ثانوية الشهيد الهادي بوعزيز بوادي العلندة وثانوية ديدي صالح بالزقم ومدى تأثرها ببعض متغيرات حسب متغير الجنس (ذكر، أنثى) ومتغير الشعبة (أدبي ، علمي) وطبقت العينة على 100 تلميذ وتلميذة تم اختيارهم بطريقة عشوائية من كلا المؤسستين من ولاية الوادي وقد تمثلت أداة الدراسة في مقياس الاتجاه نحو خدمة الإرشاد يتضمن 32 عبارة ، كما استخدمنا المنهج الوصفي في عملية جمع المعلومات وتحليلها وقد خلصت الدراسة الى النتائج التالية: - طبيعة الاتجاه نحو خدمة الارشاد النفسي من وجهة نظر تلاميذ السنة ثانية ثاني باتجاه ايجابي . - لا توجد فروق بين تلاميذ السنة ثانية ثانوي بين الذكور والإناث على مقياس الاتجاه نحو خدمة الارشاد النفسي. - لا توجد فروق بين تلاميذ السنة ثانية ثانوي على مقياس الاتجاه نحو خدمة الارشاد النفسي بين الشعب ( أدبي ، علمي) This study aimed to identify the nature of the attitudes of secondary school students, especially second-year secondary school students at Chahid Hedi Bouaziz Secondary School in Oued El Anada and Didi Saleh Secondary School in Al-Zoqm, and the extent to which they are affected by some variables according to the gender variable (male, female) and the section variable (literary, scientific). The sample was applied to 100 male and female students. They were selected randomly from both institutions in the state of El Oued. The study tool was a scale of attitudes toward counseling service that included 32 statements. We also used the descriptive approach in the process of collecting and analyzing information. The study concluded with the following results: - The nature of the trend towards psychological counseling service from the point of view of second year students is second positive. - There are no differences between second-year secondary school students, males an
Keywords: الارشاد النفسي; اتجاهات التلاميذ